(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2020)
This article is about the content and structure of the Harmony class, along with a number of features that are relevant today. In order to develop the ability to dialectically accept music, it is necessary to create conditions for the formation of musical impressions in simulated processes that develop creativity and creative thinking.